A comparative study of different types of dielectric trapezoid optical waveguides under weak guidance approximation - Srivastava S.K.; Ojha S.P. (My University, 2025)
In this communication, we present a comparative study of different types of dielectric trapezoidal waveguides. Using a numerical method, we obtain the modal characteristic equations of these trapezoidal waveguides. The modal characteristic equations are obtained in this case by using a point-matching method under the weak guidance approximation. Dispersion curves are also obtained. The modal characteristics of trapezoidal waveguides are compared with those of square waveguides in detail. Some important insights have been obtained, which are distortions of a square shape into a trapezoidal shape responsible for the slight increase in the lowest cutoff value (Vc); the distortion from a square shape to a trapezoidal shape is also responsible for the increase in the number of modes. This study can be viewed as a tolerance study of the waveguide with the square cross section under a trapezoidal distortion.